2017
DOI: 10.1089/ars.2016.6642
|View full text |Cite|
|
Sign up to set email alerts
|

Lysyl Oxidase Induces Vascular Oxidative Stress and Contributes to Arterial Stiffness and Abnormal Elastin Structure in Hypertension: Role of p38MAPK

Abstract: Aims: Vascular stiffness, structural elastin abnormalities, and increased oxidative stress are hallmarks of hypertension. Lysyl oxidase (LOX) is an elastin crosslinking enzyme that produces H 2 O 2 as a by-product. We addressed the interplay between LOX, oxidative stress, vessel stiffness, and elastin. Results: Angiotensin II (Ang II)-infused hypertensive mice and spontaneously hypertensive rats (SHR) showed increased vascular LOX expression and stiffness and an abnormal elastin structure. Mice over-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 63 publications
4
89
0
2
Order By: Relevance
“…The contribution of Lox to arterial stiffness is confirmed with smooth muscle specific Lox overexpressed mice, which show higher vascular stiffness, but normal blood pressure (656). ANG II further enhances vascular Lox expression, and BAPN reduces ANG II-induced arterial stiffness, oxidative stress, and p38 MAPK activation in mice (656).…”
Section: Ang II Mechanisms Of Arterial Stiffnessmentioning
confidence: 85%
“…The contribution of Lox to arterial stiffness is confirmed with smooth muscle specific Lox overexpressed mice, which show higher vascular stiffness, but normal blood pressure (656). ANG II further enhances vascular Lox expression, and BAPN reduces ANG II-induced arterial stiffness, oxidative stress, and p38 MAPK activation in mice (656).…”
Section: Ang II Mechanisms Of Arterial Stiffnessmentioning
confidence: 85%
“…For example, while it has been shown that the downregulation of LOX contributes to the aortic stiffening in an obesity mouse model (Chen et al., 2013), other studies have shown that inhibition of LOX attenuated the angiotensin II induced aortic stiffening (Eberson et al., 2015). In addition, as evidence showed that genetic deletion or functional deficiency of LOX causes aortic wall destruction and leads to aortic stiffening (Lee et al., 2016; Maki et al., 2002; Staiculescu et al., 2017), a smooth muscle cell‐specific overexpression of LOX in a mouse model has been shown to induces arterial stiffness (Martinez‐Revelles et al., 2017). Although the reasons for these inconsistencies are unclear, one potential explanation may arise from the distinct extracellular and intracellular effects of LOX.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reasons for these inconsistencies are unclear, one potential explanation may arise from the distinct extracellular and intracellular effects of LOX. Although it has been widely accepted that mature active LOX functions in the extracellular cross‐linking of collagens and elastin, this active form of LOX has also been detected to be increased inside the VSMCs and is able to stimulate intracellular signaling pathways as detected in LOX transgenic mice (Martinez‐Revelles et al., 2017). In addition, it has been reported that LOX‐PP participates in the regulation of the focal adhesion kinase in cancer cells (Zhao et al., 2009), although its biological activity in VSMC remains to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown the critical contribution of LOX to the control of endothelial homeostasis 1619 and to the regulation of vascular remodeling by modulating cell proliferation, ECM calcification and ROS production 15,20,28 . Neointimal thickening induced by carotid artery injury was attenuated in a transgenic mouse model that specifically over-expresses LOX in VSMC, consistent with the lower proliferative rates exhibited by VSMC from these animals 20 .…”
Section: Discussionmentioning
confidence: 99%